2010
DOI: 10.1097/yct.0b013e3181c1881f
|View full text |Cite
|
Sign up to set email alerts
|

Electroconvulsive Therapy for Catatonia in Neuropsychiatric Systemic Lupus Erythematosus

Abstract: Neuropsychiatric systemic lupus erythematosus encompasses neurological syndromes of the central, peripheral, and autonomic nervous system and a variety of psychiatric syndromes. Neuropsychiatric systemic lupus erythematosus presenting as catatonia is uncommon, and treatment of this condition is not well defined. Here we describe a case of neuropsychiatric systemic lupus erythematosus with catatonia and our treatment approach focusing on electroconvulsive therapy in conjunction with cyclophosphamide. We also di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…After a thorough PubMed search in January 2013 and after checking all of the cross references, we could find only 22 cases of catatonic symptoms in SLE reported in the literature. Details of 19 such cases [4][5][6][7][8][9][10][11][12][13][14][15] are shown in Table 1. We were unsuccessful in obtaining details of three case reports.…”
Section: Discussionmentioning
confidence: 99%
“…After a thorough PubMed search in January 2013 and after checking all of the cross references, we could find only 22 cases of catatonic symptoms in SLE reported in the literature. Details of 19 such cases [4][5][6][7][8][9][10][11][12][13][14][15] are shown in Table 1. We were unsuccessful in obtaining details of three case reports.…”
Section: Discussionmentioning
confidence: 99%
“…18 ECT has also been reported to be of use in SLE patients with catatonia, 8,19Y21 including hyperkinetic and akinetic mutism. 22 More recently in 2010, Fam et al 10 reported the treatment of a case of NPSLE with catatonia with ECT in conjunction with cyclophosphamide.…”
Section: Discussionmentioning
confidence: 98%
“…reported an experience with ECT in a patient with severe psychosis, mania, and catatonia, also with excellent results. 9 Subsequently, other cases of successful use of ECT as an adjunct therapy in severe neuropsychiatric lupus were published 1012 that included the use of ECT in juvenile SLE presenting with catatonia and severe depression. 2,1315 Table 1 provides a detailed review of all cases reported in the literature.…”
Section: Discussionmentioning
confidence: 99%